Racialized Equity Labor, University Appropriation and Student Resistance. (13th May 2019) - Lerma, Veronica; Hamilton, Laura T; Nielsen, Kelly
Abstract: We coin the term "racialized equity labor" to describe the often uncompensated efforts of people of color to address systematic racism and racial marginalization within organizations. Using a year-long ethnographic and interview study of a majority-minority public university, we focus specifically on the racialized equity labor of college students who, like many faculty and staff of color, often labor to make their campuses comfortable and functional for historically underrepresented populations. We identify a cycle of racialized labor appropriation whereby: 1) people of color identify problems in the racial environment of their organizations and work to solve them; 2) leadership responds by blocking efforts and/or denying issues; 3) external and/or internal pressures force introspection and push leaders to resolve an organizational threat (e.g., to the university's public image of diversity); and finally, 4) leadership appropriates racialized equity labor, and in doing so converts it into a diluted diversity initiative. Those engaged in racialized equity labor may resist appropriation, but the cycle takes a toll on activists. The ways in which organizations respond to racialized equity labor offers insight into the reproduction of racial inequities, despite the hard work of people of color to create meaningful racial change.